Molecular and Functional Characterization of Three Different Postzygotic Mutations in PIK3CA-Related Overgrowth Spectrum (PROS) Patients: Effects on PI3K/AKT/mTOR Signaling and Sensitivity to PIK3 Inhibitors. - Daria C Loconte; Valentina Grossi; Cristina Bozzao; Giovanna Forte; Rosanna Bagnulo; Alessandro Stella; Patrizia Lastella; Mario Cutrone; Francesco Benedicenti; Francesco C Susca; Margherita Patruno; Dora Varvara; et al. (PLoS ONE, 2015)
PIK3CA-related overgrowth spectrum (PROS) include a group of disorders that affect only the terminal portion of a limb, such as type I macrodactyly, and conditions like fibroadipose overgrowth (FAO), megalencephaly-capillary malformation (MCAP) syndrome, congenital lipomatous asymmetric overgrowth of the trunk, lymphatic, capillary, venous, and combined-type vascular malformations, epidermal nevi, skeletal and spinal anomalies (CLOVES) syndrome and Hemihyperplasia Multiple Lipomatosis (HHML). Heterozygous postzygotic PIK3CA mutations are frequently identified in these syndromes, while timing and tissue specificity of the mutational event are likely responsible for the extreme phenotypic variability observed.We carried out a combination of Sanger sequencing and targeted deep sequencing of genes involved in the PI3K/AKT/mTOR pathway in three patients (1 MCAP and 2 FAO) to identify causative mutations, and performed immunoblot analyses to assay the phosphorylation status of AKT and P70S6K in affected dermal fibroblasts. In addition, we evaluated their ability to grow in the absence of serum and their response to the PI3K inhibitors wortmannin and LY294002 in vitro.Our data indicate that patients' cells showed constitutive activation of the PI3K/Akt pathway. Of note, PI3K pharmacological blockade resulted in a significant reduction of the proliferation rate in culture, suggesting that inhibition of PI3K might prove beneficial in future therapies for PROS patients.